Here's the question you clicked on:
Ro_05
Use elimination to solve the system of equations. Enter your answer as an ordered pair; example: (4, -5) 2x+6y=-8 5x-3y=88
( 14, - 6) is what i got
If u multiply the second equation what do u get? @Ro_05
multiply 2 to the second equation that way you have 10x - 6y = 176 , then add the two equations together.
@Poetrylover what u got is right. it would be really better if u show the work.:)
sorry 2x +6y = -8 2(5x - 3y) = 2(88) 2x+6y=-8 10x-6y=176 12x=168 /12 /12 x=14 plug in x 2(14) +6y=-8 28+6y=-8 -28 -28 6y=-36 /6 /6 y=-6 (14, -6)